Electronic Traffic Law Enforcement: Is it Able to Reduce Traffic Violations? - Aryanindita Bagasatwika (Unnes Law Journal, 2020)
The practice of law enforcement on traffic violations committed by law enforcement officers is currently not enough to satisfy the expectations of the community. Problems often occur in current law enforcement practices, including vulnerability to corruption and convoluted bureaucracy in dealing with the process of law enforcement, especially for traffic violations. The practice of law enforcement itself cannot only be shackled in the current legal rigidity, in this condition a legal breakthrough or legal progression is needed, so that our law can adjust to the times and demands of society. The E-TLE (Electronic Traffic Law Enforcement) system created by the Semarang Traffic Police Unit is a breakthrough in law in law enforcement practices that are applied to traffic violations in the City of Semarang in order to bring a fast, precise, clean and transparent law enforcement system. In this context, progressive legal theory is used to create a breakthrough in progressive law enforcement in the E-TLE Satlantas Polrestabes Semarang system against traffic violations in the city of Semarang.